Total sulfur analysis of fine particulate mass on nylon filters by ICP–OES. Issue 3 (18th March 2020) - Dombek, Tracy; Poitras, Eric; Hand, Jenny; Schichtel, Bret; Harrington, James M.; Levine, Keith E.
Abstract: Sulfur (S) and sulfate (SO4 2− ) in fine particulate matter (PM2.5 ) are monitored by the Interagency Monitoring of Protected Visual Environments (IMPROVE) network at remote and rural sites across the United States. Within the IMPROVE network, S is determined from X‐ray fluorescence (XRF) spectroscopy from a Teflon filter, and SO4 2− is determined via ion chromatography (IC) from a nylon filter. Differences in S and SO4 2− estimates may indicate the presence of organosulfur (OS) species or biases between sampling and analytical methods. To reduce potential biases, an inductively coupled plasma–optical emission spectroscopy (ICP–OES) method was developed to allow for analysis of SO4 2− and S from a single filter extract. Sulfur (ICP–OES) and SO4 2− (IC) estimates from 2016 IMPROVE filters correlated strongly, suggesting that, on average, ICP–OES accurately estimated S. However, observed differences between slopes suggested the presence of water‐soluble OS species, especially during summer. Organosulfur species are important indicators of secondary organic aerosols formed through reactions of biogenic and anthropogenic pollutants and can be quantified through laboratory techniques such as reverse‐phase liquid chromatography (RPLC) or hydrophilic liquid interaction chromatography (HILIC) coupled to electrospray ionization–high‐resolution tandem mass spectrometry (RPLC/ESI‐HR–MS/MS and HILIC/ESI–HR–MS/MS, respectively), and field techniques using Aerodyne aerosol mass spectrometry (AMS). However, these methods are costly and introduce relatively large uncertainties when scaled for large networks such as IMPROVE. The method described in this report provides an inexpensive complement to XRF, which measures total S (insoluble and water‐soluble S) to estimate water‐soluble S and OS concentrations in PM.